Network ethnography: shifting perspectives and approaches to make sense of education governance - Avelar, Marina; Ball, Stephen J. (Práxis Educativa, 2023)
In response to the growing internationalisation and privatisation of education provision and governance, education policy research needs new tools and methods. This paper discusses theoretical and methodological adaptations needed to address new forms of governance. To do so, it draws from the literature on governance and policy mobility, and the methodological tools of Network Ethnography (NE) and following policy. Attention is shifted from structures to mobilities, focusing on new configurations of social life and relations, which are increasingly “networked”. This responsive and adaptive assemblage of research tactics and techniques addresses both the organisation and processes of network relations in the shifting terrain of new education governance. Keywords: Education Policy. Network ethnography. Governance.